A meta-analysis of the relationship between eating restraint, impaired cognitive control and cognitive bias to food in non-clinical samples. (November 2021) - Watson, Poppy; Le Pelley, Mike E.
Abstract: Aim: Food restriction is argued to be a precursor for unhealthy preoccupation with food, possibly leading to the development of an eating disorder. We updated previous meta-analyses that examined the relationship between eating restraint and deficits in either general or food-related attentional and inhibitory control. We hypothesized that inconsistencies in the literature around eating restraint, impaired cognitive control, impulsivity and cognitive biases for food could be attributed to the scale used to measure eating restraint. Method: A (preregistered) subgroup meta-analysis examined whether patterns of impaired cognitive control and cognitive bias for food in predominantly healthy (non-clinical) samples differed as a function of the scale used to measure eating restraint. A series of exploratory meta-analyses were carried out for specific attentional bias tasks. In total 57 datasets were included. Results: The subgroup analysis did not provide evidence that the relationship between eating restraint and impaired or biased cognitions differed significantly as a function of restraint scale. Heterogeneity across studies was high. When examining specific attentional bias tasks there was no evidence that increased eating restraint was associated with increased attentional bias or distraction by food cues, regardless of which scale was used to measure eating restraint. Conclusions: There is little experimental evidence for the common narrative that increased eating restraint is related to impaired cognitive control generally or increased cognitive bias for food, in non-clinical samples. Highlights: Food restriction is argued to lead to an unhealthy preoccupation with food. Attentional and behavioural biases for food are increased in eating-disorder populations. These 'cognitive biases' were investigated in non-clinical samples using meta-analysis. No evidence that increased eating restraint is related to increased cognitive bias for food.